ETHNOGRAPHIC STUDY OF ARM STRENGTH TRAINING PRACTICES IN THE PENCAK SILAT COMMUNITY CASE STUDY AT TAPAK SUCI MARTIAL ARTS SCHOOL - Fadillah, Reihan; Topo Yono; Rizki Apriliyanto (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
This study aims to explore arm strength training practices within the Pencak Silat community, focusing on Tapak Suci Martial Arts School at Universitas Muhammadiyah Jember. This research employs a qualitative descriptive method with an ethnographic approach, allowing an in-depth exploration of training techniques, routines, and practitioner experiences. The findings reveal that Tapak Suci's traditional training methods—such as bodyweight exercises, striking hard objects, and lifting natural weights—are still widely practiced and play a crucial role in building endurance and mental resilience. However, these methods lack structured progression and explosive power development, which are essential for modern competitive fighting. The study also finds that modern training techniques, including resistance band exercises, weightlifting, and plyometric drills, offer scientifically-backed advantages in muscle strength enhancement. The integration of both traditional and modern methods can create a more effective and well-rounded training program, optimizing fighter performance while preserving Pencak Silat’s cultural identity. In conclusion, while traditional training methods remain fundamental, their integration with modern sports science techniques provides greater efficiency, strength gains, and injury prevention. Future research should explore long-term impacts of combined training approaches and assess how practitioners culturally adapt to modern techniques while maintaining the essence of traditional martial arts training.